TINJAUAN KEGIATAN PEMBERANTASAN SARANG NYAMUK (PSN) DAN INDEKS AEDES AEGYPTI INVESTATION LEVEL DI KELURAHAN PADANG SAMBIAN KAJA KECAMATAN DENPASAR BARAT TAHUN 2017 - Ni Luh Ayu Rahma Primantari; I Nyoman Gede Suyasa (Poltekkes Kemenkes Denpasar, 2018)
Abstract:The high cases of DHF are strongly influenced by environmental factors that include geographical and demographic conditions. These factors are very influential on the population density of Aedes Aegypti mosquitoes. The presence of larva Aedes Aegypti in a region is an indicator of the presence of Aedes Aegypti mosquito populations in the area so that it can lead to the occurrence of cases of DHF, therefore the eradication strategy needs to be done through mosquitoes eradication activities (PSN) by the community continuously and periodically. The purpose of this research is to know the review of Mosquito Nest (PSN) and Aedes aegypti investation level in Padang Sambian Kaja Subdistrict, West Denpasar District. The type of descriptive study with cross-sectional design. The number of samples is 97 people with random sampling method. Data collection by doing larvae and kusioner examination. Result of research got result of implementation of eradication of mosquito nest by society in sub district of Padang Sambian Kaja District of West Denpasar mostly in less category that is counted 41 person (42,3%). The index of Aedes Aegypti Infestation Level record in Padang Sambian Kaja Village is included in the high risk of HI = 82.97%, CI = 19.61%, and BI = 156.70%. Suggestion to involve the community in larva examination by forming cadres jumantik so it can perform periodic larvae examination at each region.